2007
DOI: 10.1002/ps.1437
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation behaviour of spinosad insecticide in soil, cabbage and cauliflower under subtropical conditions

Abstract: The dissipation of the insecticide from soil, cabbage and cauliflower appeared to occur in a single phase and conformed to first-order kinetics. The half-lives of spinosad residues in cabbage, cauliflower and soil were calculated as 1.5, 2.8 and 2.8 days respectively for the 17.5 g ha(-1) treatment, and as 2.6, 2.0 and 2.0 days for the 35 g ha(-1) treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 4 publications
5
21
0
1
Order By: Relevance
“…The safety interval for spinosad sprayed tomato fruit was determined to be 1.92 and 3.88 d at application rate of 15 and 30 g ai ha -1 , respectively. In addition, Sharma et al (2007) studied the residues of spinosad in cauliflower and cabbage, and found that the half-lives values were 2.8 and 1.5 d, respectively, for the 17.5 g ha -1 treatment, and as 2.0 and 2.6 d for the 35 g ha -1…”
Section: Discussionmentioning
confidence: 99%
“…The safety interval for spinosad sprayed tomato fruit was determined to be 1.92 and 3.88 d at application rate of 15 and 30 g ai ha -1 , respectively. In addition, Sharma et al (2007) studied the residues of spinosad in cauliflower and cabbage, and found that the half-lives values were 2.8 and 1.5 d, respectively, for the 17.5 g ha -1 treatment, and as 2.0 and 2.6 d for the 35 g ha -1…”
Section: Discussionmentioning
confidence: 99%
“…According to Kumar and Poehling (2007) of spinosad was comparably high in the laboratory (100% nymphal mortality at 6-9 days post application), but in the greenhouse a faster decline of activity was evident by increased egg deposition, egg hatch and reduced rates of immature mortality. Sharma et al (2007) also reported that spinosad persisted in cabbage and cauliflower up to 7 and 10 days following spinosad application at lower and higher dosages. However, spinetoram 12 SC has translaminar activity, thereby providing a relatively prolonged residual action (Yee et al, 2007).…”
Section: Persistence Of Spinetoram 12 Sc Against L Boeticus On Pigeomentioning
confidence: 97%
“…al., 2004;Mohapatra et al, 1995;Pramanik & Chatterjee, 2004;Muthukumar et al, 2007) and low residual effect with shorter waiting period for harvest of the produce (Mandal et. al., 2009;Atwa et al, 2009;Sharma et al, 2008). Earlier studies carried out by Patil (2008) in red gram production also indicated negative influence of pesticide excessive usage on the cost of cultivation in non-IPM farmer's fields thereby resulting in negative returns on net profit whereas in IPM farmers, the effect of plant protection chemicals on production was positive.…”
Section: Curd Yield and Its Economic Analysismentioning
confidence: 99%